Corridors of development in Western and Eastern Siberia - G. I. Popodko; Г. И. Поподько (Novosibirsk State University of Economics and Management, 2025)
The accelerated development of Siberia is determined by its significant role in the country’s development, both in terms of natural resource exploitation and geopolitical positioning. Currently, the development rate of the Siberian macro-region has slowed, the volume of investments is dropping and the population is decreasing. To change this situation, new spatial development tools need to be applied to the “Siberian” regions. One of the possible ways for improving regional management processes is through “corridors of development”, which is the economic space incorporating centers of economic activity with transportation, energy, and logistical infrastructure. This study is aimed at analyzing the potential for forming development corridors in specific regions of Western and Eastern Siberia, ensuring accelerated growth of their production potential, economic diversification, and improving the standard of living of the population by creating new jobs. The study identifies Novosibirsk and Kuzbass corridors in Western Siberia and the Krasnoyarsk Arctic, Krasnoyarsk Southern, and Irkutsk corridors in Eastern Siberia as the prospective development corridors. Ускоренное развитие Сибири обусловлено ее значимой ролью в развитии страны как с точки зрения освоения природных богатств, так и использования геополитического положения. В настоящее время темпы развития Сибирского макрорегиона замедлились, падает объем инвестиций, наблюдается заметное сокращение численности населения. Для изменения сложившейся ситуации необходимо применить новые инструменты пространственного развития «сибирских» регионов. Одним из них являются «коридоры развития», которые представляют собой экономическое пространство, объединяющее центры экономической активности с транспортной, энергетической, логистической инфраструктурой. Целью настоящего исследования является анализ возможностей формирования коридоров развития в отдельных регионах Западной и Восточной Сибири, обеспечивающих ускоренный рост их производственного потенциала, диверсификацию ...